2016
DOI: 10.1534/genetics.116.186791
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Orthogonal Signaling by the Notch and Dpp Pathways in Drosophila

Abstract: The transcription factor Suppressor of Hairless and its coactivator, the Notch intracellular domain, are polyglutamine (pQ)-rich factors that target enhancer elements and interact with other locally bound pQ-rich factors. To understand the functional repertoire of such enhancers, we identify conserved regulatory belts with binding sites for the pQ-rich effectors of both Notch and BMP/Dpp signaling, and the pQ-deficient tissue selectors Apterous (Ap), Scalloped (Sd), and Vestigial (Vg). We find that the densest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 121 publications
(148 reference statements)
0
12
0
Order By: Relevance
“…On the ventral side, DL and Twist (TWI) activate but SNA represses the expression in the mesoderm [39,44]. Expression on the dorsal side is inhibited directly by Suppressor of hairless (Su(H)), which is the only known repressor of sim in the neuroectoderm [45], but is believed to have an activating influence on sim in the mesoderm region [45,48,49].…”
Section: Quantifying and Interpreting The Value Of Perturbation Expermentioning
confidence: 99%
“…On the ventral side, DL and Twist (TWI) activate but SNA represses the expression in the mesoderm [39,44]. Expression on the dorsal side is inhibited directly by Suppressor of hairless (Su(H)), which is the only known repressor of sim in the neuroectoderm [45], but is believed to have an activating influence on sim in the mesoderm region [45,48,49].…”
Section: Quantifying and Interpreting The Value Of Perturbation Expermentioning
confidence: 99%
“…Our first use of the 1344 SUH-RBs was to identify the SUH-RB with the densest cluster of Smad Dpp/BMP-effector, Apterous, and Zelda binding sites (Stroebele and Erives 2016). This led to the identification of the nab dorsal wing margin enhancer (DWME) Stroebele and Erives (2016). A single SUH-RB at Notch and one of the Delta SUH-RBs also contained a similar set of sites as the nab DWME.…”
Section: Su(h)-dependent Enhancers At Notch and Deltamentioning
confidence: 99%
“…In addition to the Notch and Delta WMEs, we cloned and tested 11 SUH-RBs and found that 10 of these drove distinct tissue-specific activities, which we show in this study and companion studies (nab DWME (Stroebele and Erives 2016) and 9 novel enhancers in the upper and bottom halves of Table 4, respectively). In a companion study on the regulation of nab developmental gene (Stroebele and Erives 2016), we found that a SUH-RB containing two Su(H) sites in the first intron on nab corresponds to a wing/haltere imaginal disc enhancer (DWME) and a larval brain enhancer (BrE) ( Table 4). The nab DWME is licensed by wing disc selectors to integrate Notch and Dpp/BMP signaling pathways and drive expression in the dorsal wing margin.…”
Section: Identification Of Novel Suh-rb Enhancers From Different Stagesmentioning
confidence: 99%
“…The smallest possible scale to ascribe such homology is that of individual nucleotide positions ("site positional homology"). Of course this is possible only in the context of homological inference based on multiple nucleotide positions in a sequence.By studying the function and evolution of regulatory DNA sequences (transcriptional enhancers in Ciona and Drosophila), which are not constrained by rigid, protein-coding, triplet reading frames (Erives et al Brittain et al 2014;Stroebele and Erives 2016), I conclude that site positional homology is incorrectly handled by gapped alignment (GA). GA was originally adopted by necessity in order to compare protein sequences of divergent lengths (Braunitzer's gappy comparisons of α-and β-hemoglobin…”
mentioning
confidence: 99%
“…This issue is exacerbated to great extremes in the regulatory DNAs of the speciose Hawaiian Drosophila (Brittain et al 2014;O'Grady and DeSalle 2018). Nonetheless, this issue also is seen for the sequences encoding many important regulator proteins enriched in polyglutamine content and other repeats, including the Notch intracellular domain and sub-units of the Mediator complex (Tóth-Petróczy et al 2008;Fuxreiter et al 2008;Rice et al 2015;Stroebele and Erives 2016;Erives 2017). As a related consequence, repeat alleles at these loci are not being accurately genotyped by modern genome assembly despite evidence of profound phenotypic effects (Rice et al 2015;Chandler et al 2017;Press and Queitsch 2017;Press et al 2019).…”
mentioning
confidence: 99%